On the binding of aminoalkyl adenylates to isoleucyl-tRNA synthetase from Escherichia coli MRE 600. - Flossdorf, J (1977)
The binding of nine aminoalkyl adenylates to isoleucyl-tRNA synthetase from Escherichia coli MRE 600 was measured and compared with the binding of the cognate amino acids. It was found that they bind rather tightly to the enzyme, the Kd's ranging from 3.1.10(-4) M with glycinol-AMP ester to 3.7.10(-9) M with L-isoleucinol-AMP ester. The binding is not affected by magnesium. It is shown that the free energies of binding of the esters can be calculated adding a constant contribution of the AMP-moiety of about - 4.1 (- 17) kcal/mole (kJ/mole) to the free energies of binding of the cognate amino acids, which we have reported earlier (19, 25, 26).